Redefining Black Beauty in a Children’s Book - Erica Maxwell; Jessica Ann Alexander (Humanities)
This essay explores the journey of co-authoring the children’s book Beauty With A Birthmark (2022) inspired by my experiences as a Black mother and those of my Black daughter, the main character in the book. Our book examines themes of beauty and self-acceptance, challenging traditional beauty standards and promoting the need for continually creating space for Black main characters in children’s books. Our essay further highlights the underrepresentation of Black protagonists in childhood picture books, acknowledging the pivotal role of gatekeepers in the publishing industry. We also address the impact of inclusive literature in classrooms and school libraries as it relates to Black children’s self-esteem, appreciation of and exposure to diversity, and academic achievement. Through this lens, Beauty With A Birthmark fosters belonging and confidence among young Black readers, illustrating the far-reaching influence that representation in children’s literature embodies.